Prognostic factors after pulmonary metastasectomy of colorectal cancers: influence of liver metastasis. Issue 1 (December 2016) - Kim, Seok; Kim, Hong; Cho, Jong; Choi, Yong; Kim, Kwhanmien; Kim, Jhingook; Zo, Jae; Shim, Young; Heo, Jin; Lee, Woo; Kim, Hee
Abstract Background Our objective was to evaluate the influence of liver metastasis on survival after pulmonary metastasectomy in patients with colorectal cancer (CRC). Methods We retrospectively reviewed a total of 524 patients and were classified into two groups based on the presence of liver metastasis. Group HM + PM (n = 106) included patients who previously received a hepatic metastasectomy and then received pulmonary metastasectomy. Group PM (n = 418) included patients who only received pulmonary metastasectomy with no liver metastasis. Results There were more male patients (70 vs. 57 %;P = 0.02) and more patients with colon cancer (60 vs. 42 %, P = 0.001) in group HM + PM than in group PM. Otherwise, there was no significant difference between the two groups in clinicopathologic characteristics and extent of surgery. The 5-year overall survival (OS) and disease-free survival (DFS) rates were 58 and 31 %, respectively. There was no significant difference in OS (group HM + PM, 54 % vs. group PM, 59 %;P = 0.085) and in DFS (group HM + PM, 28 % vs. group PM, 32 %;P = 0.12). For the entire patient cohort, a multivariate analysis revealed that the presence of liver metastasis, CRC T and N stages, disease-free interval, and number and size of lung metastases were significantly associated with OS and DFS. Conclusions Our findings suggest that previous or present liver metastasis should not exclude a patient from pulmonary metastasectomy. When lung metastasis is detected in patients with a history of hepatic metastasectomy, pulmonary metastasectomy is still a viable treatment option especially in patients with a long disease-free interval and a small number of lung metastases.